2021
DOI: 10.21273/jashs05086-21
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Characteristics of Petalized Anther Abortion in Male Sterile Camellia oleifera Plants

Abstract: Petalized anther abortion is an important characteristic of male sterility in plants. The male sterile plants (HB-21) evincing petalized anther abortion previously discovered in a clone population of the Camellia oleifera cultivar Huashuo by our research group were selected as the experimental material in this study. Using plant microscopy and anatomic methods and given the correspondence between external morphology and internal structure, we studied the anatomic characteristics of petalized anther abortion (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…The petaloid-type CMS in C. oleifera 'X1' has also been reported in previous studies [10]. The anthers of petaloid-type male-sterile C. oleifera plants produce little or no pollen, which is helpful for leveraging heterosis as female parents [10,11]. Thus, understanding the mechanism of male sterility through the study of abortive anthers contributes to improving the traditional breeding strategies of C. oleifera.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…The petaloid-type CMS in C. oleifera 'X1' has also been reported in previous studies [10]. The anthers of petaloid-type male-sterile C. oleifera plants produce little or no pollen, which is helpful for leveraging heterosis as female parents [10,11]. Thus, understanding the mechanism of male sterility through the study of abortive anthers contributes to improving the traditional breeding strategies of C. oleifera.…”
Section: Introductionsupporting
confidence: 55%
“…Previous studies have reported that the petalized male sterility of C. oleifera may be related to premature or late degradation of the tapetum [10,11]. However, the physiology of calcium accumulation and reactive oxygen species during abortive anther development remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…C. oleifera is a widely distributed plant species in southern China [ 1 ], with a planting area of more than 4.5 million hectares [ 48 ]. The C. oleifera industry is rapidly expanding and developing, becoming one of the main industries for rural revitalization in China [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pollen is a crucial carrier of genetic information in angiosperms and is released from the pollen sac after anther dehiscence [1][2][3]. Pollen morphology is strictly genetically regulated, and the pollen of different species or varieties has certain morphological recognition features that are widely employed in studies such as taxonomy or palynology [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have shown that C. oleifera pollen viability is as high as 83% [18,19]. However, later studies on C. oleifera asexual lines showed pollen viability ranging from 40 to 60% [1,10,17,20,21]. It thus appears that the yield-oriented selection in the breeding process reduces the pollen viability of the selected C. oleifera varieties.…”
Section: Introductionmentioning
confidence: 99%